Web macerası (WEBQUEST) yönteminin canlılarda üreme büyüme ve gelişme ünitesindeki kavram öğrenmeye olan etkisi - MERTOĞLU, HATİCE (My University, 2022)
Bu çalışmanın amacı fen bilimleri dersi “Canlılarda Üreme, Büyüme ve Gelişme” ünitesinde kullanılan web macerası (webquest) yönteminin öğrencilerin kavram öğrenmesine olan etkisini araştırmaktır. Araştırma deseni olarak ön-test son-test uygulamalı deney ve kontrol gruplarıyla yapılan yarı deneysel modeldir. Veriler 2018- 2019 eğitim öğretim yılında Gaziantep ilindeki bir devlet okulunda öğrenim gören öğrencilerden toplanmıştır. Araştırmaya 7.sınıfa devam eden 65 öğrenci katılmıştır. Çalışmanın verileri, SPSS 23.0 paket programı ile analiz edilmiştir. Araştırmanın sonucunda web macerası yönteminin, ünitedeki kavramların doğru anlaşılmasında mevcut öğretim programındaki etkinliklere göre daha etkili olduğu tespit edilmiştir. Çalışmada Web macerasının öğrencilerin kavram öğrenmelerine olumlu etkisi bulunduğundan Fen bilimleri dersindeki diğer ünitelerde kullanılması önerilmektedir. Pandemi nedeniyle uzaktan eğitime geçişin yaşandığı son günlerde diğer branşlarda kullanılması eğitimin kalitesi ve öğrenci katılımı bakımından olumlu yönde bir katkı sağlayacağı düşünülmektedir. Bu uygulama okulun bilgisayar sınıfında gerçekleştirilmiş ve iki öğrenci bir bilgisayarı dönüşümlü olarak kullanmıştır. Bundan sonra yapılacak çalışmalarda web macerasının daha etkin uygulanabilmesi şartların daha iyi olduğu ortamlarda kullanılması önerilmektedir.

From the past to the present, many different materials have been used to provide education to everyone and to everywhere. Today, the most preferred method among these materials is technology. Internet-based learning methods are developed in order to enable students to access accurate and reliable information in line with the needs of the 21st century. Web adventure method is one of them. The aim of the research is to study the effect of the webquest method used in the unit of "Reproduction, Growth and Development in Living Beings" on the students' concept learning. It is a quasi-experimental model made with pre-test post-test applied experimental and control groups as a research design. The data were collected from students studying at a public school in Gaziantep in the 2018-2019 academic year. 65 students attending the 7th grade participated in the research. The data of the study were analyzed with the SPSS 23.0 package program. As a result of the research, it has been observed that the web adventure method has a great effect on the correct understanding of the concepts in the unit compared to the activities in the current curriculum. Since Web adventure has a positive effect on students' concept learning, it is recommended to be used in other units in the science course. It is thought that the use of it in other branches in the last days of the transition to distance education due to the pandemic will contribute to both the quality of education and student participation. This application was carried out in the computer classroom of the school and two students used a computer alternately. In future studies, environments where the conditions are better can be used to implement web adventure more effectively.
The effect of web adventure (WEBQUEST) method on concept learning in the reproduction, growth and development unit
Keywords: Fen bilimleri; webquest; fen eğitimi; kavram yanılgıları; Science; science education; misconceptions